Manajemen Hipertensi Pada Masyarakat di Wilayah Desa Dukuhlo Kabupaten Tegal - Nurhakim Yudhi Wbowo; Susi Muryani; Deni Irawan; Syarifudin Bachtiar; Agung Laksana Hendra Pamungkas (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension can cause serious helath problems. The high incidence of hypertension needs to be controlled properly. One way to manage to manage it is by detecting non-communicable diseases (NCDs), especially hypertension, as early as possible and providing immediate treatment. This became the basis for the community service activity conducted by the Nursing Science and Professional Nurse Program of Universitas Bhamada Slawi through a hypertension screening program. The aim of this activity was to provide health checks to encourage behavior change toward a healthy lifestyle through promotive and preventive efforts against hypertension. The method used in this program included health checks for the people in Dukuhlo Village, blood pressure checks, healthy walks, exercise, and health education. The results showed a decreased in blood pressure after the healthy walk and exercise activities. About 82% of participants did not experience hypertension, while 18% still had high blood pressure. Based on this community service, hypertension can be managed through physical activity, medication, and education. This program can be continued regularly by health cadres in Dukuhlo Village.